ENVIRONMENTAL, SOCIAL DAN GOVERNANCE (ESG) DAN PROFITABILITAS PADA NILAI PERUSAHAAN - Wardah R Aulia; Christina Verawati Situmorang (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
The objective of this study is to examine and analyze the influence of Environmental, Social, and Governance (ESG) factors as well as Profitability on Firm Value among companies listed in the SRI-KEHATI index during the 2019–2023 period. The study sample includes 13 companies consistently listed in the SRI-KEHATI index throughout the observation period. The sampling technique employed is purposive sampling, resulting in a total of 65 units of analysis (13 companies × 5 years). The data analysis method used is multiple linear regression with the assistance of SPSS version 27. The results of the study indicate that ESG and Profitability variables simultaneously influence Firm Value by 45.9%. The remaining 54.1% is influenced by other variables outside the scope of this research model, such as firm size, capital structure, company growth, liquidity, institutional ownership, business risk, as well as external factors including interest rates, inflation, and government policies—all of which may affect firm value but were not examined in this study. Partially, the three ESG components (Environmental, Social, and Governance) do not have a significant effect on Firm Value. Meanwhile, Profitability, measured by Return on Assets (ROA), has a positive and significant effect on Firm Value